Sustainability business in the culinary sector: A systematic literature review - Yudawisastra, Helin G; Layalia, Faza (Social Agriculture, Food System, and Environmental Sustainability, 2025)
Background: Business sustainability issues arise in the culinary sector due to the need to balance growth with environmental, social, and economic impacts. The purpose of this study is to analyze the business strategies used by culinary businesses to achieve sustainability. Methods: This research uses the Systematic Literature Review (SLR) method with the PRISMA protocol. Literature searches were conducted on the Google Scholar database using keywords such as "sustainability business," "culinary business," and "Indonesia." Using Harzing's Publish or Perish application, 17 articles were selected that met the criteria. Finding: This research uses the Systematic Literature Review (SLR) method with the PRISMA protocol. Literature searches were conducted on the Google Scholar database using keywords such as "sustainability business," "culinary business," and "Indonesia." Using Harzing's Publish or Perish application, 17 articles were selected that met the criteria. Conclusion: The study concludes that the sustainability of culinary businesses in Indonesia depends on the ability to integrate environmental, social, and economic strategies simultaneously. Novelty/Originality: This article provides originality by being one of the first Systematic Literature Reviews (SLR) that specifically maps sustainability strategies in Indonesia’s culinary sector using the PRISMA protocol.